UNDERSTANDING DONOR LOYALTY IN THE DIGITAL WAQF ECOSYSTEM: EXPLORING TRUST FORMATION AND PERCEIVED SOCIAL IMPACT IN ISLAMIC SOCIAL FINANCE - Abdul Hakim; Atok Syihabuddin (Jurnal Al-Iqtishad, 2026)
The rapid growth of digital technology has transformed the landscape of Islamic social finance, particularly in the management and distribution of waqf funds. While digital platforms have improved accessibility, efficiency, and transparency, sustaining donor participation remains a critical challenge for waqf institutions. This study employed a qualitative exploratory approach using a single-case study design. Data were collected through in-depth interviews with waqf donors and institutional managers, supported by observations and document analysis. The data were analyzed using thematic analysis to identify recurring patterns and relationships among key concepts. The findings reveal that digital transparency serves as the primary foundation for trust formation. Transparent financial reporting, accessible program information, visual documentation, and responsive digital communication enhance donors' confidence in the institution. Furthermore, perceived social impact emerged as a crucial factor in strengthening emotional attachment and long-term commitment. Donors were more likely to remain loyal when they perceived that their waqf contributions generated tangible and sustainable social benefits. The study also found that donor loyalty develops through a sequential process linking digital transparency, trust, perceived social impact, emotional attachment, and sustainable participation. This study contributes to the Islamic social finance literature by extending Trust Theory into the context of digital waqf and proposing a conceptual model that explains the formation of donor loyalty.